Re-thinking Innovation in Organizations in the Industry 4.0 Scenario: New Challenges in a Primary Prevention Perspective - Palazzeschi, Letizia; Bucci, Ornella; Di Fabio, Annamaria (Frontiers in Psychology, 2018)
In organizations, innovation is considered a relevant aspect of success and long-term survival. Organizations recognize that innovation contributes to creating competitive advantages in a more competitive, challenging and changing labor market. The present contribution addresses innovation in organizations in the scenario of Industry 4.0, including technological innovation and psychological innovation. Innovation is a core concept in this framework to face the challenge of globalized and fluid labor market in the 21st century. Reviewing the definition of innovation, the article focuses on innovative work behaviors and the relative measures. This perspective article also suggests new directions in a primary prevention perspective for future research and intervention relative to innovation and innovative work behaviors in the organizational context.